Evidence for the Periplasmic Location of Hydrogenase in Desulfovibrio gigas - Bell, George R. (1974)
Hydrogenase has been found to be located in the periplasmic space of Desulfovibrio gigas, and it is proposed that hydrogenase plays an important and specific role in interspecies hydrogen transfer.